Clinicopathological Features and ICD-10 Categorization of Oro-maxillofacial Surgical Biopsies from Sulaimani - Hamied, Marwa Abdul-Salam; Hasanain Hafid Kudeir; Dena Nadhim Mohammad; Ban Falih Ibraheem; Balkees Taha Garib (AL-Kindy College Medical Journal, 2023)
Background: Few updated retrospective histopathological-based studies in Iraq evaluate a comprehensive spectrum of oro-maxillofacial lesions. Also, there was a need for a systematic way of categorizing the diseases and reporting results in codes according to the WHO classification that helps occupational health professionals in the clinical-epidemiological approach. Objectives: to establish an electronic archiving database according to the ICD-10 that encompasses oro-maxillofacial lesions in Sulaimani city for the last 12 years, then to study the prevalence trend and correlation with clinicopathological parameters. Subjects and Methods: A descriptive-analytical study included the archived records from three major histopathological centers in Sulaimani (College of Dentistry, Shahid Saifaldeen, and Shorsh Hospitals), related to surgical biopsies of oro-maxillofacial lesions performed between 2008 and 2019 in Sulaimani. Data were tabulated in an excel sheet and analyzed. Results: This study involved 2100 oro-maxillofacial lesions, male: female ratio was 1:1.2, and a mean age of 41.03±19.51 years old. The most frequently involved sites were; the lip (14.5%), followed by the gum and alveolar ridge (14.2%). 69.4% of cases were non-neoplastic lesions. The neoplastic lesions were significantly (P=.000) observed in old patients with a mean age of 46.1±21.09, mostly epithelial tumors (39.1%), followed by connective tissue tumors (19.5%). Malignant connective tissue tumors were more frequently seen than benign ones (52.5% versus 47.5%). The non-neoplastic lesions revealed predominate soft tissue lesions (45.2%), followed by salivary gland diseases (13.8%), with a mean age of 38.26±18.8. Squamous cell carcinoma was the most common epithelial tumor, while haemangioma was predominant among connective tissue tumors Conclusions: ICD-10 classification of oro-maxillofacial lesions in Sulaimani city helps establish a standardized coding database system for clinicopathological distribution. However, the majority of recorded lesions were non-neoplastic especially diagnosed as soft tissue lesions. Still, neoplastic lesions with their minor distribution deserve great attention as they threaten patients’ lives.